2008
DOI: 10.7202/016957ar
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Return-to-Work among Employees Absent Due to Mental Health Problems

Abstract: The contribution of work in the occurrence of mental health problems prompts us to question the conditions which favour a successful return to work. The goals of this study are to describe the profile of workers who have been absent due to a mental health problem and to compare those who returned to those who did not, and those for whom there was resolution or non resolution of their health problem. This study among public sector employees was cross-sectional. Data was collected using mailed questionnaires and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 31 publications
1
10
0
5
Order By: Relevance
“…a combination of both elements). These results corroborate those of St-Arnaud et al [36], who found that more than 90% of workers absent from work due to a mental health problem gave full or partial work-related reasons to explain the worsening of their health status and their sick leave. Similarly, 61% of workers who participated in Quebec's Investigation on Work, Employment and Health Conditions considered their depressive symptoms to be partially or completely related to their principal job [10].…”
Section: Discussionsupporting
confidence: 94%
“…a combination of both elements). These results corroborate those of St-Arnaud et al [36], who found that more than 90% of workers absent from work due to a mental health problem gave full or partial work-related reasons to explain the worsening of their health status and their sick leave. Similarly, 61% of workers who participated in Quebec's Investigation on Work, Employment and Health Conditions considered their depressive symptoms to be partially or completely related to their principal job [10].…”
Section: Discussionsupporting
confidence: 94%
“…Pour ces personnes dont le trouble de santé mentale s'est manifesté en cours d'emploi, parfois pour la première fois, le retour au travail est une étape cruciale. En effet, dans plusieurs cas, le travail a contribué, de manière plus ou moins importante, à la détérioration de l'état de santé 11 . Le retour au travail fait alors partie d'un processus continu à travers lequel la santé du salarié se reconstruit graduellement, influencée par l'activité de travail elle-même 12 .…”
Section: L'accommodement : Une Réponse Aux Besoins Des Personnes Soufunclassified
“…Ainsi, les modifications apportées à l'environnement psychosocial de travail peuvent s'avérer déterminantes, tant pour permettre l'intégration au travail des personnes souffrant d'un handicap mental grave que pour favoriser la réussite de la réinsertion professionnelle des employés qui se sont absentés pour des problèmes transitoires. Qui plus est, elles se traduisent invariablement par le renversement des facteurs de risque à la santé mentale de tous [11][12][13] .…”
Section: L'accommodement : Une Réponse Aux Besoins Des Personnes Soufunclassified
“…Il demeure toutefois important que les gestionnaires interagissent avec les intervenants externes pour eux-mêmes mieux intervenir auprès de l'employé en deuil, et ce, en vue de faciliter son retour au travail (Holmgren et Ivanoff, 2007;James, Cunningham et Dibben, 2006). Enfin, outre les facteurs organisationnels susmentionnés qui influencent le retour au travail, quelques auteurs évoquent plus rarement l'importance des programmes d'aide aux employés (Hazen, 2008), de la reconnaissance (St-Arnaud et al, 2007), de la culture organisationnelle (Hazen, 2006;James, Cunningham et Dibben, 2006), de l'évaluation positive du travail (St-Arnaud et al, 2007), de la représentation syndicale des travailleurs (James, Cunningham et Dibben, 2006) Rhéaume, 2003;Wasiak et al, 2007).…”
Section: Problématiqueunclassified